THE ROLE OF LAW IN NATIONAL ECONOMIC DEVELOPMENT: A LITERATURE STUDY ON THE RELATIONSHIP BETWEEN REGULATION AND PUBLIC WELFARE - Irma Rachmawati Maruf; Mohamad Khairi Bin Haji Othman (Adisam Publisher, 2025)
This research aims to analyse the role of law in national economic development through a literature study on the relationship between regulation and public welfare. Law functions as a normative framework that provides certainty, protection of rights, and guidelines for economic actors in creating a conducive and equitable investment climate. This study uses normative legal research methods by examining laws and regulations, government policies, and literature related to economic development law in Indonesia. The results of the study show that regulatory harmonisation, consistent law enforcement, and integration of social justice values in every economic policy are the main prerequisites for promoting inclusive economic growth and improving people's welfare. However, regulatory disharmony is still a challenge that can hamper the effectiveness of public policies and reduce the quality of services to the community. Therefore, optimising the role of Pancasila economic law, strengthening coordination between agencies, and public participation in the legislative process are needed so that national economic development truly contributes to the achievement of social justice and shared prosperity.